The assessment of the quality of welded joints made of abrasion-resistant plates using the nanocrystalline filler metal (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
The article presents the analysis of the structure and properties of joints made of abrasion-resistant plates having the structure of chromium cast iron and welded with filler metals, the use of which aimed to provide the high abrasion resistance of the surface layer and good mechanical properties of the base material. The face layer of the joint was made using the MMA (Manual Metal Arc) welding method and the Fe-Cr-Nb-B type nanocrystalline filler metal. The root weld was made using an austenitic plastic filler metal, whereas the filling layer was made using the MAG welding method and a low-alloy filler metal. The joints were subjected to non-destructive tests (visual tests and penetrant tests) as well as destructive tests. The research involved macro and microscopic metallographic tests, the determination of the grain size using an Xpert PRO X-ray diffractometer and the analysis of the chemical composition of precipitates performed using a scanning electron microscope provided with an EDS attachment. The assessment of the operational properties of the joints was based on hardness measurements, static tensile tests and bend tests as well as on tests identifying the metal-mineral abrasive wear, performed in accordance with ASTM G65 – 04. The results of the abrasion resistance tests were referred to the properties of steel HARDOX 400. The tests revealed that the filler metals used in the tests can be used when joining abrasion-resistant plates, providing the latter with appropriate operational properties.